Antioxidante enzimático en jóvenes y adultos de la Facultad de Farmacia y Bioquímica de la Universidad Nacional de Trujillo - Chavez Ordoñez, Yelsin Wuendi (2018)
The objective of the present study was to determine the enzyme antioxidant in youth and adults of the Faculty of Pharmacy and Biochemistry, for which 50 fasting volunteers of both sexes belonging to the administrative and student staff, young people 18 to 29 years old and adults participated. from 30 to 65 years old, they signed an informed consent and filled out a survey, then obtained the blood samples obtaining the serum, then the determination of the enzymatic antioxidant was made: catalase enzyme by means of the Aebi method based on the decomposition of hydrogen peroxide ( H2O2) in water and oxygen. The results were evaluated obtaining: of the total of volunteers 66% were women, 30% presented values and 36% high, 34% were male, 24% presented normal values of catalase and 10% elevated. Regarding the age of the total of volunteers, 76% were young, 34% had normal values of catalase activity and 42% had high values. 34% were adults, 30% presented normal values of catalase activity and 4% elevated. The enzymatic antioxidant was compared according to the type of diet considering 5 variables: consumption of flours, red meats, white meats, vegetables and dairy products, reaching the conclusion that the consumption of vegetables favors the activity of catalase, the consumption of red meats and flours diminishes this activity and favors the formation of free radicals